How I cope at university: Self‐directed stress management strategies of Australian students. (6th May 2021) - Reis, Arianne; Saheb, Rowena; Parish, Patricia; Earl, Andrea; Klupp, Nerida; Sperandei, Sandro
Abstract: Universities across the world remain under‐resourced and frequently unequipped to provide the required support to the increasing demand of students experiencing mental health problems. While there is a considerable amount of research focusing on university student stress levels, interventions to address them, and coping strategies adopted by students, little research has reported on the strategies students choose to manage their stress and how that relates to their self‐identified sources of stress as well as to what universities are offering to support their mental health and wellbeing. The present study provides a contribution in this direction, reporting on a study that surveyed over 3200 students from three large Australian metropolitan universities and interviewed three groups of university staff who provide student wellbeing services. Results highlight differences between what students and staff perceive as main sources of stress and best strategies to address them. In addition, students recommend task‐oriented, pro‐active coping strategies more often to their peers than engage in them themselves. The findings of the study further reinforce the need to develop an understanding of student coping strategies with a lens considerate of students' perspectives and preferences to authentically support their wellbeing, better informing planning and service delivery.